ANALYSIS OF STUDIES ON THE EPIDEMIOLOGICAL AND CLINICAL PROFILE OF PATIENTS TREATED BY PHYSIOTHERAPY: LITERATURE REVIEW (CIPEEX, 2025)
Epidemiology investigates the distribution and determinants of diseases, with a view to prevention and control. This research addresses the integration between epidemiological profile and physiotherapy practices, examining different clinical contexts. The objective is to explore how epidemiological profiles influence physiotherapy intervention strategies, based on a descriptive and quantitative literature review of articles published between 2008 and 2019. The aim was to evaluate the epidemiological profile of patients in different physiotherapy care contexts and discuss the importance of physiotherapy in these scenarios. The review analyzed studies of patient records in health institutions, such as hospitals, clinics, and meatpacking plants. Articles that presented relevant epidemiological and clinical data were selected, with specific inclusion and exclusion criteria. The studies showed that burn patients are at high risk of nosocomial infections, highlighting the need for physical therapy to prevent complications. Meatpacking plant workers reported musculoskeletal disorders, highlighting the importance of preventive physical therapy. Patients in higher education institutions presented degenerative conditions, predominantly among older women. Physical therapy is crucial for the rehabilitation and prevention of chronic conditions and complications in different contexts. The analysis of epidemiological profiles should guide physical therapy practices, adapting interventions to the specific needs of the populations served. Future studies are needed to improve intervention strategies and optimize patients' quality of life.
Keywords: epidemiological profile; physical therapy; prevention; rehabilitation